Escolha e preferência por alimentos com ou sem valores calóricos em crianças com deficiência intelectual e sobrepeso - Macedo, Marina Zanoni (Universidade Federal de São Carlos, 2011)
Obesity and pre-obesity have been considered as one of the major health problems in modern society, both in developed and in developing countries is the increase in rates of overweight or obese individuals. Although much is known about the types of foods that contribute to it, few results have been observed in the control of impulsivity commonly involved in food intake behavior. This study investigated whether the caloric component of food and its magnitude have control over choice behavior and preference in subjects ranging from seven to thirteen years old, with overweight and intellectual developmental delay. The research was conducted in a charity institution specialized in serving individuals with intellectual developmental delay. Two identical gums were prepared for this study, in relation to the organoleptic characteristics, differing only for the calories they contain. For data collection, we used an experimental apparatus that operated in concurrent chain schedule of reinforcement. The first link was operating on values of fixed ratio (FR- 1), followed by another scheme, also operating in FR-1. The schedules were controlled by a computer program. Choice responses in Button 1 were followed by one caloric gum in its terminal link, and choice responses in Button 2 were followed by a non-caloric gum in its terminal link. The session consisted of four presentations of the schedules. The data of interest were the responses in the initial links of concurrent chain schedules. A single subject design was applied, with the participant as his own control. The results, first, illustrated that there was no preference for calorie-rich foods, and will be considered as baseline for continuing the study, in which each of the possible variables controlling food choice could be introduced (eg, delay of reinforcing contingency , cost of response). Studies on the nature of choice and preference for non-caloric and caloric foods are important to identify and describe appropriate procedures for understanding and controlling food intake in overweight or obese children with intellectual developmental delay.
Keywords: Psicologia; Análise do comportamento; Obesidade; Escolha (Psicologia); Escolha alimentar; Crianças; Deficiência intelectual; Food choice; Obesity; Children; Intellectual developmental delay; CIENCIAS HUMANAS::PSICOLOGIA